Ekstraksi Lipida Dengan Metode Microwave Assisted Extraction Dari Mikroalga Yang Potensial sebagai Biodiesel - Bintari, Yoni Rina; Haryadi, Winarto; Rahardjo, Tri Joko (JU-ke: Jurnal Ketahanan Pangan, 2018)
Important stages of the production of biodiesel from microalgae is a lipid extraction step. Microwave Assisted Extraction (MAE) is an extraction technique utilizing microwave energy using water solvent. Excellence MAE method is to minimize the use of organic solvents that are toxic, no ecofriendly and unrenewable. Extraction of lipids from microalgae using MAE method leads to a green process to produce bioenergy. This study aims to obtain the optimum extraction conditions of S. platensis lipids and T. chuii using MAE method, the effect of the addition of n-hexane at a post extraction and conversion to biodiesel.Â The results showed that the optimum of lipid extraction conditions from S. platensisÂ  at microwave power of 560 Watts, the addition of water to the volume of microalgae 6.67 mL/gram dry weight of S. platensis and extraction time of 510 seconds resulting lipid yield of 1.27%. The optimum of lipid extraction condition from T. chuii at 800 Watts of power, the addition of water to the volume of microalgae 8.3 mL/gram dry weight T. chuii and extraction time for 510 seconds resulting lipid yield of 1.25%. Increasing the number of n-hexane at a post extraction from S. platensis effective in adding volume 5 mL, where the addition of 7 mL to 15 mL have no significant increase in yield. Conversion of S. platensis lipids and T. chuii produced a high yield of biodiesel in comparison to the amount of lipid methanol 1:173 to yield 66,7% and 75% respectively.